Participation of annexin 1 in the response of Arabidopsis thaliana to lead exposure: potential for phytoremediation - Phang, Ing Chia; Leung, David W. M.; Clark, Gregory B.; Taylor, Harry H.; Garrill, Ashley; Song, Jason; Roux, Stanley J. (2009)
Heavy metal pollution has become a serious public health and environmental concern. Lead (Pb) is one of the heavy metals known to bioaccumulate in plants. Phytoremediation is an emerging technology based on the ability of green plants to remove Pb from the environment in a cost-efficient and ecologically sound manner. Currently, an important research focus is to seek a better understanding of the mechanisms of Pb tolerance by plant cells, with the aim of genetically engineering plants with improved tolerance to Pb, and hence better phytoremediation capabilities in the near future.